The primacy of social over visual perspective-taking - Moll, Henrike; Kadipasaoglu, Derya (Frontiers in Human Neuroscience, 2013)
In this article, we argue for the developmental primacy of social over visual perspective-taking. In our terminology, social perspective-taking involves some understanding of another person’s preferences, goals, intentions etc. which can be discerned from temporally extended interactions, including dialogue. As is evidenced by their successful performance on various reference disambiguation tasks, infants in their second year of life first begin to develop such skills. They can, for example, determine which of two or more objects another is referring to based on previously expressed preferences or the distinct quality with which these objects were jointly explored. The pattern of findings from developmental research further indicates that this ability emerges sooner than analogous forms of visual perspective-taking. Our explanatory account of this developmental sequence highlights the primary importance of joint attention and the formation of common ground with others. Before children can develop an awareness of what exactly is seen or how an object appears from a particular viewpoint, they must learn to share attention and build common “experiential“ ground. Learning about others’ as well as one’s own “snapshot“ perspectives in a literal, i.e., optical sense of the term, is a secondary step that affords an abstraction from all (prior) pragmatic involvement with objects.